Réponses

2012-10-15T17:48:12+02:00

C=(27x10^8)/(15x10^6x12x10^(-5)^3)

C=(27x10^8)/(15x10^6x12x10^(-15))

C=(27x10^8x10^15)/(15x6x12x10^6)

C=(3x3x3x10^23)/(3x5x2x3x3x2x2x10^6) on simplifie par 3x3x3

C=(10^23)/(5x2x2x2x10^6)

C=(10^23)/(4x10x10^6)

C=(10^23)/(4x10^1x10^6)

C=(10^23)/(4x10^7)

C=(1/4)(10^23)/(10^7)

C=(1/4)(10^16)=0.25x10^16=25x10^14

 

D=(54x10^(-17)x35x(10^4)^3)/(14x10^16x12x(10^(-6)^2))

D=(54x35x10^(-17)x10^12)/(14x16x12x10^16x10^(-12))

D=(54x35x10^(-5))/(14x16x12x10^4)

D=(2x3x3x3x5x7)/(2x7x2x2x2x2x2x2x3x10^4x10^5) on simplifie par 2x3x7

D=(3x3x5)/(2x2x2x2x2x2x10^9)

D=45/(64x10^9)=(45/64)x10^(-9)